PENINGKATAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN IPS DENGAN PENDEKATAN PENGAJARAN LANGSUNG - ROHANA, Siti (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
This study originated from the reality on the SDN 11 Luhak Nan Duo, students have difficulty learning because learning IPS,IPS Teachers have been using a variety of learning activities in the IPS. For that class action research conducted using direct teaching approach. Pendektan used in this study is Kualikatif and quantitative approach to research design class action. Subjects were Fourth Grade Students of SDN 11 Luhak Nan Duo procedures performed research planning, implementation, observation and reference. The results I encounter I RPP cycle 62%, 63% Teacher aspects, aspects of students 61%, 65.99 learning outcomes. I Cycle 2 meeting RPP 81%, 78% Teacher aspects, aspects of students 76%, 80 learning outcomes. In the second cycle RPP 87%, 93% Teacher aspects, aspects of students 91%, 81.57 learning outcomes. Kata kunci : Hasil belajar siswa dalam pembelajaran IPS